Moose (Alces alces) browsing patterns in recently planted clear-cut areas in relation to predation risk of the gray wolf (Canis lupus) in Sweden - van Beeck Calkoen, Suzanne (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2016)
The aim of this study was to test whether behaviorally mediated effects of gray wolf (Canis lupus) presence were visible in terms of browsing intensity by moose (Alces alces) on tree saplings in recently planted clear-cut areas in Sweden. The study involved two different spatial scales; the clear-cut scale and tree scale. At the clear-cut scale the influence of wolf predation risk, tree density and tree height on moose browsing intensity was evaluated. At the individual tree scale, the factor distance to the nearest forest edge was also included. Browsing intensity was measured as apical shoot browsing and lateral shoot browsing in 24 different recently planted clear-cuts. Due to differences in preference between tree species and qualitative differences between plant parts, the same analyses were conducted for the five main tree species and for apical and lateral shoot browsing separately. Based on pellet group counts, moose is most likely the main browser in this study. Further, I found that both tree density and tree height were lower in the wolf core areas, suggesting multicollinearity between wolf utilization, tree density and tree height at the clear-cut scale, the effect of these factors could not be separated in the multivariate models. At the clear-cut scale browsing intensity decreased with tree density. At the tree scale, although wolf utilization was an important factor explaining the variation in browsing intensity, the browsing probability decreased with tree height. Overall, this suggests that moose foraging and thus its browsing intensity was more influenced by tree density and tree height than predation risk by wolves. It also seemed that moose browse through a clear-cut area irrespectively of distance to the closest forest edge.